One-year follow up of three Italian patients with Duchenne muscular dystrophy treated with ataluren: is earlier better?. (November 2018) - Ruggiero, Lucia; Iodice, Rosa; Esposito, Marcello; Dubbioso, Raffaele; Tozza, Stefano; Vitale, Floriana; Santoro, Lucio; Manganelli, Fiore
Background: Ataluren was approved for the treatment of nmDMD, both the efficacy and safety have been previously reported only from clinical trials but no report exists about real-life experience. Patient/methods: we describe three Italian children with nmDMD treated with ataluren for 1 year. Measurements were made every 3 months and was evaluated the 6-Minute Walking Distance (6MWD). Results: Case1 involves a patient with a 6MWD at T0 of 360 m, who started ataluren therapy at age 10 years. Case2 is a child who began treatment with ataluren at age 8 years when he had severe ambulatory compromise (6MWD < 75 m at T0). A third patient (case3) had a 6MWD of 320 m when he started ataluren therapy at age 5 years. The best improvement in 6MWD was observed in case3, a patient in whom treatment with ataluren was started much earlier. In case1, ataluren was started relatively late and 6MWD was maintained at a stable level. Surprisingly, we observed a 50% improvement in 6MWD in case2, a patient who began therapy early, but with a severe loss of lower limb muscle function at the time. Conclusions: treatment responses depend on the patient's age and disease severity when therapy was initiated. On the basis of our experience, the main factor that influences the effectiveness seems to be earlier instigation of therapy and positive results may still be achieved in patients with more severe muscle involvement. Interestingly, these three boys with phenotypically different nmDMD provide useful information regarding future therapeutic recommendations for the ataluren administration in real clinical practice.